Impact of the war in Ukraine on resilience, protective, and vulnerability factors - Kimhi, Shaul; Eshel, Yohanan; Marciano, Hadas; Adini, Bruria (Frontiers in Public Health, 2023)
War or armed conflict is one of the most severe human-made adversities. The current study examines the resilience, protective and vulnerable coping factors of a sample of Ukrainian civilians, during the current Russian-Ukrainian war. The level of resilience and coping indicators were compared with the responses of an Israeli sample following an armed conflict in May 2021. The data were collected by an internet panel company. A representative sample of Ukrainian residents (N = 1001) responded to an online questionnaire. A stratified sampling method was employed regarding geographic distribution, gender, and age. The data concerning the Israeli population (N = 647) were also collected by an internet panel company during a recent armed conflict with Gaza (May 2021). Three notable results emerged in this study: (a) the Ukrainian sample reported significantly higher levels of the following: Distress symptoms, sense of danger, and perceived threats, compared with the Israeli sample. However, despite these harsh feelings, the Ukrainian respondents reported substantially higher levels of hope and societal resilience compared, to their Israeli counterparts, and somewhat higher individual and community resilience. (b) The protective coping factors of the respondents in Ukraine (level of hope, well-being, and morale), predicted the three types of resilience (individual, community, and social) better than the vulnerable coping factors (sense of danger, distress symptoms, and level of threats). (c) the best predictors of the three types of resilience were hope and well-being. (d)The demographic characteristics of the Ukrainian respondents hardly added to the prediction of the three types of resilience. It appears that a war that threatens the independence and sovereignty of a country may, under certain conditions, enhance the societal resilience and hope of the population under risk, despite a lower sense of well-being and higher levels of distress, sense of danger, and perceived threats.